Quantitative Mapping of Global Research on Mobile Health Interventions for Hypertension: A Bibliometric Study - Kamariana,; Russeng, Syamsiar S.; Arsin, Andi Arsunan; Ilham, Amil Ahmad; Hadju, Veni; Syafar, Muhammad; Kasim, Hasyim; Pawenrusi, Esse Puji; Windasari, Dewi Purnama (International Journal of Statistics in Medical Research, 2026)
Background: Mobile health (mHealth) technologies are increasingly reshaping the management of hypertension, which remains a leading contributor to global cardiovascular burden. Although a rapidly expanding body of research has explored digitally supported interventions, the structural evolution, intellectual foundations, and emerging trajectories of this field have not been comprehensively synthesized. Objective: This study aimed to map the global research landscape of mHealth interventions for hypertension and to identify the collaborative, intellectual, and conceptual structures guiding its development. Methods: A bibliometric analysis was conducted on 474 documents indexed in Scopus using VOSviewer and R Bibliometrix. Trends in scientific production were examined alongside contributions by countries, journals, authors, and highly cited documents. Co-authorship, co-citation, and keyword co-occurrence networks were analyzed to uncover the field’s knowledge architecture and thematic evolution. Results: Scientific output in mHealth intervention for hypertension has increased steadily, led by high-income countries with strong international collaboration. Highly cited studies are mainly randomized controlled trials, indicating a solid evidence base. Thematic trends show a shift from telemonitoring to scalable, patient-centred interventions, with growing focus on engagement, implementation, and equity. Conclusion: The research landscape on mHealth interventions for hypertension is rapidly advancing, with increasing methodological rigor and a shift toward scalable, patient-centred solutions. Nonetheless, disparities in global research contributions persist, underscoring the need for more inclusive and context-specific studies to support equitable implementation.